MicroRNA-98 protects sepsis mice from cardiac dysfunction, liver and lung injury by negatively regulating HMGA2 through inhibiting NF-κB signaling pathway. Issue 16 (18th August 2019) - Zhu, Jingfa; Lin, Xingyu; Yan, Cairong; Yang, Shaodong; Zhu, Zhixia
ABSTRACT: Recently, MicroRNA-98 (miR-98) works as a biomarker in some diseases, such as lung cancer, Schizophrenia, and breast cancer, but there still lack of studies on the function of miR-98 during sepsis. Thus, our study is conducted to figure out the function of miR-98 for the regulation of cardiac dysfunction, liver and lung injury in sepsis mice. Cecum ligation and puncture was used to establish the sepsis mice model. Next, miR-Con and agomiR-98 were injected into the tail vein of mice 48 h after modeling. Then, expression of miR-98, HMGA2, NF-κB, inflammatory factors, apoptosis-related proteins in myocardial, liver and lung tissues of septic mice were determined. Moreover, other indices that were associated with cardiac dysfunction, liver and lung injury in septic mice were detected. Finally, bioinformatics analysis and luciferase activity assay were utilized to validate the binding site between miR-98 and HMGA2. miR-98 was poorly expressed, while HMGA2, NF-κB pathway-related proteins were highly expressed in myocardial, liver, and lung tissues of mice with sepsis. Upregulated miR-98 inhibited HMGA2, NF-κB, TNF-α, IL-6, Bcl-2 and increased IL-10, Cleaved caspase-3 and Bax expression in myocardial, liver, and lung tissues of septic mice. Upregulation of miR-98 decreased LVEDP, CTn-I, BNP, ALT, AST, TBIL, LDH, and PaCO2 while increased +dp/dt max, -dp/dt max, pH and PaO2 in sepsis mice. miR-98 was a direct target gene of HMGA2. Our study provides evidence that miR-98 protects sepsis mice from cardiac dysfunction, liver and lung injury by negatively mediating HMGA2 via the inhibition of the NF-κB signaling pathway.